2019
DOI: 10.1111/cea.13528
|View full text |Cite
|
Sign up to set email alerts
|

Chimeric specific antigen epitope‐carrying dendritic cells induce interleukin‐17(+) regulatory T cells to suppress food allergy

Abstract: Food allergies (FAs) affect about 2%-8% of the world's population. FA clinical symptoms vary from slight abdominal discomfort to life-threatening anaphylactic shock. 1 The basic FA pathological changes are Th2 polarization-related inflammation, including the over production of antigen (Ag)-specific IgE, Th2 cytokines (eg interleukin [IL]-4, IL-5 and IL-13), profound infiltration of eosinophils and mast cells in tissues. 2 Th2 cytokines, especially IL-4, induce plasma cells to produce IgE. IgE binds to the high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
(28 reference statements)
0
6
0
Order By: Relevance
“…However, Iida et al (33) revealed that the survival time of patients with high IL-17 mRNA expression levels was significantly longer compared with those with low IL-17 mRNA expression levels by detecting the IL-17 mRNA expression levels in the peritoneal lavage of patients with gast fric carcinoma following surgery. Previous studies have also demonstrated that tumor growth and distant metastasis in IL-17 deficient mice were significantly increased compared with those in the control group, suggesting that IL-17 could enhance the antitumor immunity of local T cells in tumors (34,35). The present study investigated the effects of IL-17 in gastric carcinoma.…”
Section: Discussionmentioning
confidence: 80%
“…However, Iida et al (33) revealed that the survival time of patients with high IL-17 mRNA expression levels was significantly longer compared with those with low IL-17 mRNA expression levels by detecting the IL-17 mRNA expression levels in the peritoneal lavage of patients with gast fric carcinoma following surgery. Previous studies have also demonstrated that tumor growth and distant metastasis in IL-17 deficient mice were significantly increased compared with those in the control group, suggesting that IL-17 could enhance the antitumor immunity of local T cells in tumors (34,35). The present study investigated the effects of IL-17 in gastric carcinoma.…”
Section: Discussionmentioning
confidence: 80%
“…This coincided with a number of studies evaluating the burden of peanut allergy and calling for improved protection for people with food allergy 69‐71 . Investigation of component IgE as a marker for ingestion, an immunological target and a discriminator with added diagnostic value also continues to be a busy area of science 72‐79 . Characteristics of infant food anaphylaxis were defined in one of the most extensive published series—hives, hypotonia and hypotension were common features in a French series with 61 infant cases, compared with 386 cases in preschool children 80 .…”
Section: Food Allergymentioning
confidence: 98%
“…[21][22][23] Xu and colleagues constructed a fusion protein consisting of an epitope of the ovalbumin (OVA) molecule and a segment of the anti-DEC205 antibody, scFv. 24 The fusion protein termed chimeric Ag peptide (CAP), specifically, binds DEC205 and present on the surface of DCs. The authors show that exposure of bone marrow-derived DCs to scFv-IC fusion protein led to DC uptake of scFv-IC and also surface expression.…”
Section: Targeted Immunotherapymentioning
confidence: 99%
“…DEC‐205 (CD205) is a 205 kDa endocytotic receptor predominantly expressed by DCs and thymic epithelial cells and is thought to act as a cell surface receptor for CpG oligonucleotides and promote DC immunoregulatory activity 21‐23 . Xu and colleagues constructed a fusion protein consisting of an epitope of the ovalbumin (OVA) molecule and a segment of the anti‐DEC205 antibody, scFv 24 . The fusion protein termed chimeric Ag peptide (CAP), specifically, binds DEC205 and present on the surface of DCs.…”
Section: Experimental Models Of Allergic Diseasementioning
confidence: 99%